Searching for the community. Agrarian reform in the Lachaqui peasant community, Canta-Lima, 1970-1980 (Historia Agraria de América Latina, 2022)
The article analyzes the communal restructuring policy of the Agrarian Reform Law, promoted by the military government of Juan Velasco Alvarado, in a historic community located in the highlands of Lima, Lachaqui. Using the perspective of the decentralized state and understanding development as a tool for state subjection, the interaction and negotiations between private and public intermediaries and populations are examined. To this end, in-depth interviews and documents collected in the community and in Lima in 2018 are used. The main argument is that the government sought a modern, collectivist and productive community, based on the claim that the community was the sole owner of the land, without understanding its dynamism or diversity and the permanent tension between the family and the collective. The policy produced significant conflict over access to land in the community, between a sector that supported the measure and another sector that defended their right to individual property. The research contributes to the discussion on agrarian reform in the communities based on a state policy that is little studied, but which is important because it sought to reform them. In this sense, it gives an account of the local impact of the agrarian reform in relation to state objectives, showing how the state operates and is (re)affirmed in people’s daily lives, as well as its reformulation by them.
Keywords: Peasant communities; communal restructuring; Lachaqui; agrarian reform; communal entreprise